Provision of Urea Fertilizer and Chicken Manure on Chemical Characteristics of Inceptisol Soil in Pangkatan District - Muhammad Rizwan; FS, Harahap (Jurnal Online Pertanian Tropik, 2021)
Inceptisol soil is an agricultural land in Indonesia, which is widely distributed, but has a problem, namely the element of N in the soil is relatively low, so it is necessary to carry out proper cultivation techniques, one of which is through the provision of balanced fertilizers, namely organic fertilizers which aim to improve soil fertility and reduce use of NPK fertilizer. This study aims to determine the effect of various kinds of organic fertilizers, namely sometimes goat and urea fertilizer on the chemical properties of Inceptisols from Pangkatan. This research was conducted in the Agrotechnology Practice Area, Faculty of Science and Technology, Labuhanbatu University, Rantau Prapat, with a height of 25 meters above the sea surface. The research was started from February 2021 to June 2021. This study used a factorial randomized block design (RBD) with 2 treatment factors. namely: Urea fertilizer factor with four levels and goat manure factor with three levels. Soil analysis parameters which include, pH H2O using the electrometric method, determination of N-total soil using the Kjehldal method, soil organic C using the Wakley and Black method. The results showed that the application of goat manure was able to increase soil N-toatal on Inceptisol Pangkatan, at a dose of U1K3 (Urea: 0.25g and goat manure: 75g) while the interaction of urea and goat manure application increased N-total soil of Rantau Inceptisol. South with a dose of U1K3 (Urea: 0.25g and goat manure: 75g).